Waste Treatment Business By Bumdesa Semambu Makmur As the Practice of Islamic Teachings About Cleanliness - Ardani Ardani; Maya Panorama; Muhammad Rusdi (Medina-te : Jurnal Studi Islam, 2023)
This research was conducted in order to empirically prove the connection between the waste treatment business run by Bumdesa Semambu Makmur Semambu Island, Indralaya District, Ogan Ilir Regency and the implementation of Islamic Economics. This research uses a qualitative method with a descriptive analysis approach. by the Ministry of Law and Human Rights of the Republic of Indonesia. The business fields that are run by Bumdesa Semambu Makmur are home industry, agriculture, serving, waste processing, rental, Village PAM, and Brokering. The main business being carried out is the processing of plastic waste which produces chopped plastic. The special benefit of the plastic waste business for the people involved in plastic waste collection activities is in the form of compensation in the form of money, for Bumdesa Semambu Makmur the benefit is the fulfillment of the raw material needs for chopped plastic which provides income for Bumdesa. The general benefit (ammah) to and from the village environment is the better level of cleanliness in residents' settlements from plastic waste, this is because residents are motivated to collect plastic waste in the hope of getting economic benefits. Keeping the environment clean is the implementation of Islamic teachings.